Carbon Nanotubes: Synthesis via Chemical Vapour Deposition without Hydrogen, Surface Modification, and Application - Nguyen Duc Vu Quyen; Dinh Quang Khieu; Tran Ngoc Tuyen; Dang Xuan Tin; Bui Thi Hoang Diem (Journal of Chemistry)
The present study describes the growth of carbon nanotubes (CNTs) from liquefied petroleum gas (LPG) on an Fe2O3/Al2O3 precatalyst via a chemical vapour deposition (CVD) process without hydrogen. The obtained multiwalled CNTs exhibit a less-defective structure with an identical external diameter of tubes of around 50 nm. The growth mechanism of CNTs suggests that the Fe2O3/Al2O3 precatalyst is reduced to Fe/Al2O3 during the synthesis process using the products of LPG decomposition, and the tip-growth mechanism is suggested. The resulting CNTs are surface-modified with potassium permanganate in the acid medium and used as an adsorbent for copper from aqueous solutions. The Langmuir and Freundlich isotherm models are employed to evaluate the adsorption data, and the maximum adsorption capacity of Cu(II) is 163.7 mg·g−1.